On a Numerical-Analytic method for second-order difference equations - Iteiwi, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For second-order difference equations, we justify the scheme of the Samoilenko numerical-analytic method for finding periodic solutions.